A simple mitochondrial targeting AIEgen for image-guided two-photon excited photodynamic therapy. Issue 17 (10th November 2017) - Jiang, Meijuan; Kwok, Ryan T. K.; Li, Xuesong; Gui, Chen; Lam, Jacky W. Y.; Qu, Jianan; Tang, Ben Zhong
Abstract : A simple AIE luminogen, IQ-TPA, with mitochondrial targeting was demonstrated for image-guided two-photon excited photodynamic therapy in cancer cells. Abstract : Two-photon excited photodynamic therapy (TP-PDT) is not only able to offer deeper penetration depth but also much more precise 3D treatment than traditional one-photon excited PDT. However, the achievement of TP-PDT requires photosensitizers with large two-photon absorption cross sections, efficient generation of reactive oxygen species, and bright two-photon fluorescence. In this work, we present a simple AIE luminogen (AIEgen), IQ-TPA, with mitochondrial targeting and susceptible two-photon excitation for image-guided photodynamic therapy in cancer cells. This feasibility of utilizing small molecular multifunctional AIEgens for TP-PDT was demonstrated together with the merits of tiny size, good cell permeability, low dark cytotoxicity and easy synthesis, showing great potential for the development of future theranostic systems.